Desert dust contribution to PM10 loads in Italy: Methods and recommendations addressing the relevant European Commission Guidelines in support to the Air Quality Directive 2008/50. (July 2017) - Barnaba, Francesca; Bolignano, Andrea; Di Liberto, Luca; Morelli, Matteo; Lucarelli, Franco; Nava, Silvia; Perrino, Cinzia; Canepari, Silvia; Basart, Sara; Costabile, Francesca; Dionisi, Davide; Ciampichetti, Spartaco; et al.
Abstract: In 2011 the European Commission (EC) released specific 'Guidelines' describing the methods to quantify and subtract the contribution of natural sources from the PM10 values regulated by the European Air Quality Directive (2008/50/EC). This work investigates the applicability to Italy of the EC-Methodology suggested for desert-dust, describes main limitations encountered and proposes specific modifications embedded within a 'revised-Methodology' to extend/improve its use. The revised-Methodology capabilities are evaluated using original, chemically-resolved mineral-dust mass concentration measurements, showing better performances in predicting timing and absolute values of the desert-dust contribution to the daily-PM10 with respect to the current EC-approach. The revised-Methodology is then translated into an automatic (user-independent) tool tailored to the expected final-users. This tool is applied over Central Italy across a 3-year long period (2012–2014), and over the whole Italian country for a calendar year (2012). The derived results confirm and extend to Italian regions never addressed before some previously observed features of the desert-dust impact over the country, such as a clear latitudinal dependence of the desert-dust impact on the yearly average PM10 (from more than 5 μg/m 3 to less than 0.5 μg/m 3, going from south to north Italy). The modifications introduced within the revised-Methodology also suggest a non-negligible role of desert-dust resuspension in areas characterized by both high traffic levels and soil sealing (urban areas and along the major Italian routes). In the Rome area, such an effect is found to add a contribution of about 2 μg/m 3 (i.e., of 20%) to the mean desert-dust load per dust day (about 10 μg/m 3 ). At the national level, this effect contributes increasing the total number of desert-dust-driven exceedances of the PM10 daily limit value even in the northern regions, where the desert-dust impact on the PM10 yearly average is otherwise limited. These results also indicate the direction for possible mitigation strategies to be applied over impacted areas. The successful implementation of the revised-Methodology over Italy suggests it could represent a valid option for a nationwide standard procedure to quantify the desert-dust contribution to PM10, promoting the homogenisation of the relevant values annually reported to the EC. Graphical abstract: Highlights: European Commission Guidelines to assess impact of desert dust on PM10 are considered. A revised-Methodology better assessing desert dust impact over Italy is proposed. The revised-Methodology is validated and translated into an automatic tool. Desert dust impact on PM10 loads over Italy is quantified. Non negligible desert dust resuspension appears to affect high traffic areas.